(untitled) (Modern education and development, 2024)
This article explores effective methodologies for teaching English in preschool educational institutions, emphasizing the unique needs of young learners. It highlights the primary objectives of early language instruction, including fostering interest, developing basic vocabulary, and improving listening and speaking skills. The study discusses play-based learning, songs, rhymes, storytelling, and Total Physical Response (TPR) as key teaching approaches. It also addresses challenges such as short attention spans and varying levels of exposure to English, offering practical solutions like interactive sessions and parental involvement. The article concludes by emphasizing the cognitive and social benefits of early language learning, underlining its importance in preparing children for future academic success.